Cerebral Circulation Time Is a Potential Predictor of Disabling Ischemic Cerebrovascular Events in Patients With Non-disabling Middle Cerebral Artery Stenosis - Chen, Zhenze; Li, Mingchun; Wu, Zhihuan; Zhang, Min; Weng, Guomei; Li, Minzi; Liao, Rongxin; Zhao, Peng; Wu, Jianming; Zhu, Shuzhen; Wang, Qing; Li, Chunguang; et al. (Frontiers in Neurology, 2021)
Patients with nondisabling middle cerebral artery (MCA) stenosis (ND-MCAS) are at risk for disabling ischemic cerebrovascular events (DICE) despite aggressive medical therapy. In this study, we aimed to verify whether cerebral circulation time (CCT) was a potential predictor of DICE in patients with ND-MCAS. From January 2015 to January 2020, 46 patients with ND-MCAS treated with aggressive medical therapy were enrolled for digital subtraction angiography (DSA) in this convenience sampling study. They were divided into the DICE (-) and DICE (+) groups based on the occurrence of DICE within 3 months after DSA. The CCT was defined as the time from the appearance of the MCA to the peak intensity of the Trolard vein during DSA. The rCCT (relative CCT) was defined as the ratio of the CCT of the stenotic side (sCCT) to the CCT of the healthy side (hCCT). The differences in sCCT, hCCT and rCCT between the two groups were analyzed with Mann-Whitney U tests. Logistic regression analysis was performed to evaluate the association between the risk factors and DICE. Receiver operating characteristic (ROC) curves were constructed to assess the predictive value of rCCT in identifying DICE in ND-MCAS patients. The results showed that DICE appeared in 5 of the 46 patients within 3 months. rCCT were significantly increased in the DICE (+) group compared with the DICE (-) group (1.08 [1.05, 1.14] vs. 1.30 [1.22, 1.54], p < 0.001). Logistic regression analysis found that prolonged rCCT was an independent positive prognostic factor for DICE (odds ratio = 1.273, p = 0.019) after adjustment for potential confounders (age, diabetes, antithrombotic use, and stenosis degree). ROC analysis showed that rCCT provided satisfactory accuracy in distinguishing the DICE (+) group from the DICE (-) group among ND-MCAS patients (area under the curve = 0.985, p < 0.001), with an optimal cutoff point of 1.20 (100% sensitivity, 97.6% specificity). In conclusion, prolonged rCCT is independently associated with the occurrence of DICE in ND-MCAS patients and may be used to identify individuals at risk of DICE.